Redefining forensic anthropology in the 21st century and its role in mass fatality investigations - Márquez-Grant, Nicholas; Roberts, Julie (Soc. Anatomy Espanola (Spanish Soc. of Anatomy), 2021)
Definitions of forensic anthropology have reflected the evolution of the discipline over the past 20 years. A commonly accepted definition is currently “the application of the science of physical or biological anthropology to the legal process” (e.g. see ABFA, 2018), although this has now expanded to include human rights cases, as part of what some have called ‘Humanitarian Forensic Action’ or ‘Forensic Humanitarianism’ (Guyomarc´h, and Congram, 2015; Cordner and Tidball-Binz, 2017; Moon, 2013; Parra et al. 2020). More recently, historical cases involving the recovery, identification and repatriation of casualties from the First and Second world wars and subsequent conflicts, have also been categorised as forensic anthropology (Loe et al., 2014, Cox et al., 2016, Emanovsky and Belcher, 2012). The expansion of the definition in these contexts recognises the need for the anthropologist to conform to the standards required by forensic genetic laboratories. He or she is required to work closely with DNA scientists and be cognisant of forensic protocols relating to chain of custody, integrity of evidence and how to minimise the risks of cross contamination and misidentifications.
http://www.eurjanat.com/web/all-issues.php